Post‐exercise cold water immersion attenuates acute anabolic signalling and long‐term adaptations in muscle to strength training. (13th August 2015) - Roberts, Llion A.; Raastad, Truls; Markworth, James F.; Figueiredo, Vandre C.; Egner, Ingrid M.; Shield, Anthony; Cameron‐Smith, David; Coombes, Jeff S.; Peake, Jonathan M.
Abstract : Key points: Cold water immersion is a popular strategy to recover from exercise. However, whether regular cold water immersion influences muscle adaptations to strength training is not well understood. We compared the effects of cold water immersion and active recovery on changes in muscle mass and strength after 12 weeks of strength training. We also examined the effects of these two treatments on hypertrophy signalling pathways and satellite cell activity in skeletal muscle after acute strength exercise. Cold water immersion attenuated long term gains in muscle mass and strength. It also blunted the activation of key proteins and satellite cells in skeletal muscle up to 2 days after strength exercise. Individuals who use strength training to improve athletic performance, recover from injury or maintain their health should therefore reconsider whether to use cold water immersion as an adjuvant to their training. Abstract: We investigated functional, morphological and molecular adaptations to strength training exercise and cold water immersion (CWI) through two separate studies. In one study, 21 physically active men strength trained for 12 weeks (2 days per week), with either 10 min of CWI or active recovery (ACT) after each training session. Strength and muscle mass increased more in the ACT group than in the CWI group ( P  < 0.05). Isokinetic work (19%), type II muscle fibre cross‐sectional area (17%) and the number of myonuclei per fibre (26%) increased in the ACT group (all P  < 0.05), but not the CWI group. In another study, nine active men performed a bout of single‐leg strength exercises on separate days, followed by CWI or ACT. Muscle biopsies were collected before and 2, 24 and 48 h after exercise. The number of satellite cells expressing neural cell adhesion molecule (NCAM) (10−30%) and paired box protein (Pax7) (20−50%) increased 24–48 h after exercise with ACT. The number of NCAM + satellite cells increased 48 h after exercise with CWI. NCAM + ‐ and Pax7 + ‐positive satellite cell numbers were greater after ACT than after CWI ( P  < 0.05). Phosphorylation of p70S6 kinase Thr421/Ser424 increased after exercise in both conditions but was greater after ACT ( P  < 0.05). These data suggest that CWI attenuates the acute changes in satellite cell numbers and activity of kinases that regulate muscle hypertrophy, which may translate to smaller long‐term training gains in muscle strength and hypertrophy. The use of CWI as a regular post‐exercise recovery strategy should be reconsidered. Abstract :